Validating Subsurface Monitoring as an Alternative Option to Surface M&V - The CO2CRC's Otway Stage 3 Injection - Jenkins, C.; Marshall, S.; Dance, T.; Ennis-King, J.; Glubokovskikh, Stanislav; Gurevich, Boris; La Force, T.; Paterson, L.; Pevzner, Roman; Tenthorey, E.; Watson, M. (2017)
Future CO 2 storage projects will require Monitoring and Verification (M & V) operations at the CO 2 storage site to understand the behavior of the CO 2 plume, including the assurance that leakage of the CO 2 has not occurred. Current surface based monitoring technologies may be unable to yield sufficient resolution or accuracy. CO2CRC, in conjunction with its Australian partners, is developing the Otway Stage 3 Project to identify and validate sub-surface monitoring techniques and configurations as a key element of a risk-based M & V program in large scale CCS projects. Subsurface monitoring approaches will be tested on a plume of CO 2 from an array of monitoring wells. Primary monitoring methods will be pressure tomography and downhole seismic, although other modalities (gravity, electromagnetic) are also being considered.